Ущільнювальне плазмове покриття для деталей газотурбіного двигуна - Зубков, Олександр Віталійович (Харківський національний автомобільно-дорожній університет, 2025)
Object research – composite sealing coating, what used to reduce radial clearance in the compressor of a gas turbine engine. The purpose of the work is to select the optimal composition of components to obtain the best set of properties of the sealing coating. Research methods and equipment – composite sealing coating was obtained by the method plasma spraying using a plasma installation UPU-3D with a plasma torch PP-25. The study of adhesion strength was carried out by the pin method. The hardness was determined using a hardness tester, porosity -by means of "Epiquant" analyzer, stability coverage at temperature 600°C - by with help ovens SNOL 2.4.2/12.5. Pictures structures received by with help microscopes MIME – 8 , «Neophot » and digital cameras "Canon". Results of the conducted research – using the data obtained, the most suitable percentage composition of the sealing coating was determined. This turned out to be composition No. 5 (50% Al, 50% BN).
Keywords: sealing coating; plasma spraying; adhesive strength; thermostatic resistance; porosity